Pengaruh Kompetensi Karyawan terhadap Manajemen Proyek di PT. Nagari Lukindo Sejahtera - Diana Sari Harahap; Heri Dia Anata Batubara; Azhar Harahap (CV. ITTC INDONESIA, 2026)
This study aims to examine the effect of employee competence on project management at PT. Nagari Lukindo Sejahtera. A quantitative approach with an associative research design was employed. Data were collected through questionnaires distributed to employees involved in project implementation and analyzed using simple linear regression with IBM SPSS Statistics. The findings indicate that employee competence has a positive and significant effect on project management. Competence, which includes knowledge, skills, and work attitudes, contributes to improving project planning, implementation, coordination, and control. The coefficient of determination shows that employee competence explains 21.8% of the variance in project management, while the remaining 78.2% is influenced by other factors outside the research model. These findings suggest that continuous competency development through training, skills enhancement, and performance evaluation can improve project management effectiveness. This study provides practical implications for human resource development and serves as a reference for future research on project management.